Clinical Study To Evaluate The Efficacy Of Ashwagandadi Leha In Ksheena Shukra With Special Reference To Oligospermia. - Banappanavar, Malagouda K; Rawal, P K; Shiraguppi, Sunita (International Research Journal of Ayurveda & Yoga, 2021)
Spermatic functions. It is multifactorial condition in more than 90% of cases , except some physical sperm defects low sperm count and poor sperm quality are the responsible for the male infertility more than 90% of cases. Sperm count less than 20mill/ml is considered as oligospermia. It is one among prime factor in the male infertility. It is defined as a subnormal concentration of spermatozoa in the penile ejaculate. It is correlated with ksheena shukra condition. It is pathological condition of shukra in which there may be reduced sperm count. In classics many shukra janaka drugs are explained in ksheena shukra condition. As Ashwagandadi leha having Vrishya property thus helps in increasing the production of spermatozoa which ultimately causes increases in sperm count useful for combating the ksheena shukra. This research work is clinical study with pre-test and post-test design, 30 patients suffering from Ksheena shukra (Oligospermia) were selected randomly for study from OPD of SDM’ Trust Ayurvedic Medical college, Terdal. Selected patients were treated with Ashwagandadi leha for 60 days 10 gms BD with milk. Follow up study was under taken for 30 days after 60 days of treatment. It was found that Ashwagandadi leha showed significant improvement in various parameters like Dorbalya (Weakness), Maithuna ashakti (Loss of interest in Coitus), Shukra Avisraga, Desire, Ejaculation, Erection, Orgasm, Sperm count and Sperm motility.